(untitled) (The Batuk, 2020)
John Clare has established himself as a poet of nature and his relationship with nature is to acknowledge the value of natural world for the wellbeing of human beings. Clare gets peace and strength when he surrenders himself into the lap of nature. Whenever he experiences unbearable pain and obstacles, he tends to communicate with nature dealing with its different shades to find the ways to tackle his problems. This article, through the lance of ecocriticism, aims to depict Clare’s efforts to maintain harmonious relationship with nature to lead meaningful and peaceful life in this world.